New Otacilia species from Southwest China (Araneae: Phrurolithidae) - Fu, Lina; Zhang, Zhisheng; Zhang, Feng (Zootaxa, 2016)
The present paper describes nine new Otacilia species from Southwest China: O. mira sp. nov. (♀, ♂) and O. pyriformis sp. nov. (♀, ♂) from Chongqing, O. papilion sp. nov. (♀, ♂) from Guizhou, O. aurita sp. nov. (♀, ♂), O. digitata sp. nov. (♂), O. leibo sp. nov. (♀, ♂) and O. ovata sp. nov. (♀, ♂) from Sichuan, O. acuta sp. nov. (♀, ♂) and O. flexa sp. nov. (♀, ♂) from Yunnan. Line drawings, photos and descriptions of all new species are presented. In addition, the 21 known Chinese Otacilia species are divided into three species groups.